2012
DOI: 10.1161/jaha.112.001594
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Idiopathic Dilated Cardiomyopathy in 29 000 Patients With Celiac Disease

Abstract: BackgroundDilated cardiomyopathy (DCM) is a rare disease of largely unknown origin. Previous studies have suggested an increased prevalence of celiac disease (CD) in patients with DCM. These studies, however, were based on a maximum of 5 patients with both CD and DCM. In the present large Swedish population-based cohort study, we examined the risk of idiopathic DCM in patients with CD determined by small-intestinal histopathology.Methods and ResultsFrom 2006 to 2008, we collected duodenal/jejunal biopsy data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…Although the association of CD with DCM has been described in many studies on adult population,[25] published data in pediatric populations are few. In a study conducted by Zahmatkeshan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although the association of CD with DCM has been described in many studies on adult population,[25] published data in pediatric populations are few. In a study conducted by Zahmatkeshan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in a recent nationwide study, it was found that patients with CD had a moderately but not statistically significantly increased risk of idiopathic DCM (HR 1.73; 95% CI, 1.00–3.00) [180]. In these patients, a GFD may have a beneficial effect with improvement of echocardiographic parameters as well as in cardiological features and quality of life [178, 181].…”
Section: Autoimmune Disorders In Celiac Diseasementioning
confidence: 99%
“…In a subsequent nationwide Swedish study, 29 000 patients with coeliac disease were followed up for the subsequent development of dilated cardiomyopathy. Compared to controls, coeliac patients had a slightly increased risk of developing dilated cardiomyopathy that fell just short of statistical significance 18. The most plausible explanation for any link between coeliac disease and dilated cardiomyopathy is that both conditions might be mediated through inflammation and autoimmune mechanisms.…”
Section: Discussionmentioning
confidence: 93%